2014
DOI: 10.1371/journal.pone.0099273
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Regional Activity in Default Mode Network in Medication-Naive, First-Episode Somatization Disorder

Abstract: BackgroundPatients with somatization disorder (SD) have altered neural activity in the brain regions of the default mode network (DMN). However, the regional alteration of the DMN in SD remains unknown. The present study was designed to investigate the regional alterations of the DMN in patients with SD at rest.MethodsTwenty-five first-episode, medication-naive patients with SD and 28 age-, sex-, education- matched healthy controls underwent a resting-state functional magnetic resonance imaging (fMRI) scan. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 65 publications
4
38
0
Order By: Relevance
“…A recent review of neuroimaging studies suggested that the DMN may play an important role in the pathophysiology of SD (Browning et al, 2011). Furthermore, a recent fMRI study has shown that there was a dissociation pattern of the anterior and posterior DMN in SD (Su et al, 2014). Our findings of increased FCS in the right ITG regarded as a core region of DMN is of particular interest (Bullmore and Sporns, 2009;Greicius et al, 2003).…”
Section: Discussionsupporting
confidence: 49%
“…A recent review of neuroimaging studies suggested that the DMN may play an important role in the pathophysiology of SD (Browning et al, 2011). Furthermore, a recent fMRI study has shown that there was a dissociation pattern of the anterior and posterior DMN in SD (Su et al, 2014). Our findings of increased FCS in the right ITG regarded as a core region of DMN is of particular interest (Bullmore and Sporns, 2009;Greicius et al, 2003).…”
Section: Discussionsupporting
confidence: 49%
“…Considering the functional convergence in prefrontal cognitions [53] and its deactivation in psychiatric patients [22,23], it is conceivable that the comprehensive cognitive and metacognitive capacities such as subjective evaluation of somatic sensory cognition might be modulated in OD patients. Furthermore, cortical modifications associated with somatoform states have been suggested in m-PFC function [9][10][11][12][13]. In the present study, we found not only prefrontal deactivation during chewing but also found associated deterioration of somatization scores in OD patients.…”
Section: Discussionsupporting
confidence: 71%
“…Neuropsychological evidence for somatization and somatoform disorders has shown cortical associations with the superior medial prefrontal cortex, temporal region, and parietal region [9][10][11][12][13]. For example, Su et al [13] reported a positive relationship between somatization subscale and bilateral superior medial prefrontal activities in patients with somatoform pain disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VBM is capable of assessing structural differences in the whole brain and avoids operational bias toward particular brain regions (Honea et al, 2005;Meisenzahl et al, 2008;Ma et al, 2012;Hu et al, 2013;Guo et al, 2014a), and fALFF is designed to detect the regional intensity of spontaneous of blood oxygen level-dependent (BOLD) signals and provides a specific measure of low-frequency oscillatory phenomena (Zou et al, 2008). Increased fALFF might reflect neural hyperactivity in the area and vice versa Liu et al, 2013;Su et al, 2014). The two approaches have been widely used to explore anatomical and functional abnormalities in a bulk of psychiatric disorders, including schizophrenia.…”
Section: Introductionmentioning
confidence: 99%